Seasonal Assessment of Heavy Metals in Water at Effluents Discharge Points into the New Calabar River, Port Harcourt, Southern Nigeria (Global Journal of Science Frontier Research, 2018)
Water samples were collected at three different effluents discharge points into the New Calabar River. The samples were digested using standard methods. The digests were subsequently examined for heavy metals concentrations using atomic absorption spectrophotometer (AAS). Heavy metals results in the samples showed Ni as the most concentrated metal with a mean value of 2.52±0.055, 1.42±0.01 and 1.275±0.045 mg/L at Iwofe, Jetty, Minipity and Police Post stations respectively, this was followed by the concentration values of Cr, which were 1.72±0.06, 2.17±0.02 and 1.355±0.015 mg/L at the Iwofe Jetty, Minipiti and Police Post sample stations respectively. The least concentrated metal observed in this study was Cd with amean range of 0.03-0.28 mg/L in the stations. This was followed by the values of Cu from the station which ranged between 0.035 -1.22 mg/L. The general order of the concentration of metals was Ni>Cr>Fe>Zn>Pb>Cu>Cd. All the metals examined in the water samples except Zn were higher than the WHO maximum standard for drinking water.
Keywords: effluents; discharge points; heavy metals; pollution; contamination